Method for synergistically preparing high-strength light ceramsite and collecting tin from tin-containing tungsten tailings and red mud
By co-tungsten tailings with red mud and using high-temperature solid phase reaction, efficient recycling of tin and preparation of high-strength light-weight ceramic particles are achieved, which solves the problems of low tin recovery and low utilization of red mud in the existing technology, and is characterized by high efficiency, economical and environmental protection.
Patent Information
- Application Number
- CN202510013454.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-30
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In the prior art, the tin recovery rate of tin-containing tungsten tailings is relatively low, the energy consumption is high, and the utilization value of roasted slag is low. At the same time, the red mud pile has a large inventory, low utilization rate and serious environmental pollution.
By co-tungsten tailings with red mud, high-temperature solid phase reaction is used to achieve efficient volatile recovery of tin, and products that meet the 700 or 800 high-strength lightweight ceramic standards are prepared.
The recovery rate of tin is improved to more than 95%, the energy consumption of roasting is reduced, the high-value utilization of roasting slag is realized, and the problem of red mud is solved, which is of great economic and environmental significance.
Smart Images

Figure BDA0005229122040000071 
Figure BDA0005229122040000072 
Figure BDA0005229122040000081
Abstract
Description
Technical Field
[0001] The invention relates to a method for co-processing tin-containing tungsten tailings and red mud, and in particular to a method for co-processing tin-containing tungsten tailings and red mud to prepare high-strength lightweight ceramsite and collect tin, belonging to the technical field of solid waste resource utilization. Background Art
[0002] As an important nonferrous metal, tin is widely used in electronics, metallurgy, chemical industry and other industries. As a key component of welding materials, tin plays an indispensable role in electronic equipment, communications, semiconductors and other fields. Tin is also widely used in bronze alloys, tin plating, catalysts and other fields. It also plays an irreplaceable role in machinery, shipbuilding, sculpture, chemical industry and other fields. At present, domestic tin resources are relatively scarce and mainly rely on imports. Although there are certain tin ore resources in the valley, the grade is relatively low. With the increasing depletion of high-quality tin ore, the supply of domestic tin resources is facing great pressure.
[0003] Tungsten tailings in some areas of the country contain tin resources of a certain grade and in huge reserves. However, due to the fineness of the embedded particles, it is difficult to achieve effective recycling and utilization with traditional flotation technology. Fire reduction volatilization to recover tin has become a feasible means, but direct reduction roasting is difficult to destroy the garnet shell that wraps the tin, and the low alkalinity causes the roasting temperature to exceed 1000°C, and the tin recovery rate is only about 80%. The roasting slag can only be used as cement admixture because it has not achieved the mineral phase transformation exceeding 1300°C to 1450°C, and the blending ratio is less than 10%, resulting in limited disposal of the roasting slag and failure to achieve high-value utilization.
[0004] Red mud is an alkaline solid waste produced during the production of alumina by the Bayer process. China produces more than 80 million tons of red mud each year, but the comprehensive utilization rate is less than 10%, causing multiple hazards to the environment and resources, including leachate contamination of groundwater, land pressure from stockpiling, dust pollution and potential dam breach risks. In order to reduce the stockpile of red mud, R&D personnel are actively exploring ways to comprehensively utilize red mud, including using it as building materials such as cement, ceramsite, and concrete raw materials, but the problems of alkalinity and safety need to be solved.
[0005] So far, there has been no report on the technology of synergizing tin-containing tungsten tailings with red mud to prepare high-strength lightweight expanded clay and collect tin. If the synergistic resource treatment of tin-containing tungsten tailings and red mud can be achieved, it will be of great significance to ensure the sustainable utilization of the country's tin resources and solve the problem of tailings and red mud storage. Summary of the invention
[0006] Aiming at the technical problems of low tin recovery rate, high energy consumption and low utilization value of roasted slag in the method of pyrometallurgical reduction volatilization of tin-containing tungsten tailings in the prior art, as well as large red mud stockpile, low utilization rate and serious environmental pollution, the purpose of the present invention is to provide a method for preparing high-strength lightweight ceramsite and recovering tin by synergizing tin-containing tungsten tailings and red mud. The method makes full use of the mineral composition characteristics of the two solid wastes, tin-containing tungsten tailings and red mud, and combines the two through high-temperature solid-phase reaction, so as to achieve efficient volatilization recovery of tin and obtain high-quality ceramsite products that meet the standard requirements of 700 or 800 high-strength lightweight coarse aggregate (GB / T17431.1-2010), truly realizing the resource utilization of the two solid wastes. Compared with the simple process of high-temperature volatilization of tin-containing tungsten tailings to collect tin, not only the tin recovery rate is improved, but also no tailings are generated, and the added value is greatly improved. It is of great significance for the construction of tailing-free mines and the disposal of red mud, and the process economic feasibility is extremely high.
[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing high-strength and lightweight ceramsite and recovering tin by synergistically preparing tin-containing tungsten tailings and red mud. The method comprises the following steps: mixing raw materials including tin-containing tungsten tailings, red mud, coal powder, silicon powder, quicklime, silicon carbide and ceramsite powder with water to form balls to obtain balls; after the balls are dried, they are transferred into a rotary kiln and mixed with external coal to complete two-stage roasting; during the roasting process, tin products are recovered from the flue gas; and the solid products obtained by roasting are subjected to physical separation to separate the ceramsite products.
[0008] The key to the present invention is to carry out high-temperature roasting treatment on tin-containing tungsten tailings and red mud. According to the composition of ceramsite raw materials, red mud has the characteristics of high content of iron, aluminum, sodium and other phases, and it just complements the silicon, aluminum, sodium, calcium and other phases with the tin-containing tungsten tailings. The requirements of ceramsite components can be met by adjusting the ratio of raw materials, and the aluminum, sodium, calcium and other phases in the red mud can induce the destruction of the garnet shell that wraps tin in the tin-containing tungsten tailings, thereby promoting the volatilization of tin. At the same time, the higher iron content in the red mud also gives magnetism to the ceramsite, which is beneficial to the subsequent separation of ceramsite and coal powder. More specifically, garnet in tin-containing tungsten tailings wraps tin and hinders its reduction and volatilization behavior at high temperatures, and it is combined with red mud with high iron, aluminum and sodium content for synergistic high-temperature treatment, which promotes the decomposition and transformation of garnet by increasing the content of aluminum, sodium and calcium phases. Among them, sodium, calcium and other phases can generate low-melting-point silicate liquid phases to reduce the liquid phase formation temperature and the viscosity of the system in the roasting system. In particular, the sodium phase, as a strong alkaline oxide, has a particularly significant fluxing effect and will form albite, sodium silicate and other phases. Aluminum, calcium and other phases provide additional aluminum and calcium sources to enhance the bridging of aluminum, calcium and silicon oxygen in the system, making the silicon oxygen tetrahedral network structure in garnet unstable and causing the reorganization of the silicate framework. In addition, the aluminum phase participates in the formation of ceramsite-supported skeleton mullite, spinel and other phases, and the calcium phase participates in the formation of calcium silicate (such as C2S, C3S) and other phases. The decomposition of garnet successfully released the tin components contained therein, thereby improving the volatilization recovery efficiency of tin. And because the raw material composition meets the basic range requirements of the three components of ceramsite silicon, aluminum, and alkaline metal oxides given by the Riley triangle, the liquid phase can be regulated by controlling the temperature, thereby further making ceramsite in the tin recovery process.
[0009] In the process of coordinated treatment of tin-containing tungsten tailings and red mud of the present invention, required auxiliary materials are also added, such as coal powder, silicon powder, quicklime, silicon carbide and ceramsite powder, which are beneficial to the formation of ceramsite and the promotion of tin volatilization; among them, silicon carbide mainly plays a foaming role, mainly to make up for the consumption of part of coal powder participating in reduction reaction and decomposition during high-temperature roasting; the ceramsite powder is mainly to avoid the generation of solid waste, and the unqualified ceramsite is returned to the ceramsite preparation process after being crushed, and its addition has almost no effect on the performance of the ceramsite; quicklime mainly plays a bonding role. Since the tin-containing tungsten tailings are in the form of fine sand and have extremely low viscosity, a binder needs to be added for use. Compared with bentonite, quicklime can also provide a calcium source. The regulation of calcium can reduce the roasting temperature and promote the formation of some calcium silicate phases, which is helpful for the alkali excitation effect in the later production of ceramsite concrete, and can also promote the separation of garnet. The decomposition and conversion are beneficial to the volatilization of tin; the pulverized coal as the main reducing component not only acts as a reducing agent and provides a CO reducing atmosphere, which is beneficial to the conversion of tin into easily volatilized stannous oxide and improves the volatilization recovery efficiency of tin, but also is the main foaming component. The residual pulverized coal that is not consumed in the tin reduction stage continues to be thermally decomposed at high temperature in the second stage of ceramsite expansion to produce gas, which promotes the foaming of ceramsite together with the gas produced by the decomposition of silicon carbide; the role of silicon powder is to supplement the silicon content of the system. The silicon component not only participates in the formation of mullite, spinel and other phases of the ceramsite supporting skeleton, but is also the main component of the glass phase. The glass phase is a typical low-melting-point substance. By controlling the proportion of the glass phase by adjusting the silicon content, the formation temperature of the low-melting-point substance can be indirectly controlled, and the metal flux can be coordinated with the ceramsite expansion temperature to be above the optimal volatilization temperature of tin, and the ceramsite roasting temperature can be reduced as much as possible under the premise of achieving a clear distinction between the two processes.
[0010] As a preferred solution, the raw materials include the following components by mass: 60-75 parts of tin-containing tungsten tailings, 20-35 parts of red mud, 3-5 parts of coal powder, 5-10 parts of silicon powder, 3-7 parts of quicklime, 1-2 parts of silicon carbide, and 10-15 parts of ceramsite powder. The ratio of tin-containing tungsten tailings and red mud needs to meet the basic requirements of the ceramsite phase composition. At the same time, the ratio of red mud must also ensure that the proportion of iron components in the ceramsite raw materials is high, so that the ceramsite can be given a strong magnetic property, which is conducive to subsequent magnetic separation. Silicon carbide plays a foaming role in the system, mainly to make up for the consumption of part of the foaming material coal powder participating in the reduction reaction and decomposition in the first roasting interval, so its proportion needs to be added in an appropriate amount according to the proportion of coal powder. The incorporation ratio of ceramsite powder is mainly determined based on the output, and all incorporation can be achieved within the preferred range, thereby reducing the generation of solid waste. If the amount of quicklime added is too low, the material's cohesiveness will deteriorate, making it difficult to form balls or easy to pulverize during the drying process. If the amount of quicklime added is too low, the temperature of the liquid phase will be too low, which will cause serious kiln caking and affect production. For example, lowering the kiln temperature will lead to incomplete tin volatilization. If the coal powder content is too low, the reducing atmosphere inside the ceramsite will weaken, resulting in the need for internal tin reduction to rely on the internal diffusion of the reducing gas outside the ball, increasing the internal tin reduction process, prolonging the reduction roasting time, and worsening the reduction effect, reducing the tin recovery rate. When the coal powder content is too high, the residual amount after the ceramsite firing is too high, affecting the physical properties of the ceramsite.
[0011] As a preferred solution, the tin content of the tin-containing tungsten tailings is 0.4-0.6wt.%, the Fe2O3 content is 5-10wt.%, the SiO2 content is 45-60wt.%, the Al2O3 content is 5-10wt.%, and the CaO content is 5-10wt.%. As a preferred solution, the Fe2O3 content of the red mud is 20-30wt.%, the SiO2 content is 5-15wt.%, the Al2O3 content is 12-20wt.%, the CaO content is 5-15wt.%, and the Na2O content is 4-8wt.%. As the main raw materials for preparing expanded clay, the chemical compositions of the existing tin-containing tungsten tailings and red mud are complementary in terms of the contents of silicon, aluminum, sodium, calcium and other phases. For example, tin-containing tungsten tailings have high silicon content, low aluminum content and low sodium content, while red mud has low silicon content, high aluminum content and high sodium content. The two are matched in appropriate proportions to fully meet the requirements for the formation of major ceramic phases such as mullite and spinel. In addition, the iron content in red mud must reach a certain amount, because in addition to participating in the reaction to form phases such as fayalite, its main function is to be magnetized and reduced to ferroferric oxide, which makes the ball magnetic and facilitates its separation from bituminous coal.
[0012] The quicklime of the present invention is digested in water, resulting in a significant increase in volume. In order to avoid damage to the ceramsite raw balls during the ball making process, the quicklime can be digested first.
[0013] As a preferred solution, the fineness of the tin-containing tungsten tailings satisfies the mass content of -200 mesh particle size ≥ 70%.
[0014] As a preferred solution, the fineness of the red mud satisfies that the mass content of -100 mesh particle size is ≥ 75%.
[0015] As a preferred solution, the fineness of the coal powder satisfies the mass content of the -100 mesh particle size ≥ 85%.
[0016] The particle sizes of the tin-containing tungsten tailings, red mud and coal powder are controlled within an appropriate particle size range, which is beneficial to the subsequent pelletizing and high-temperature roasting processes.
[0017] As a preferred solution, the ball making is realized by a disc granulator, and the ball making controls the particle size of the ball material within the range of 6 to 9 mm. The disc granulator has the characteristic of uniform ball making. Since the particle size distribution of ceramsite is required to be narrow, in order to ensure stable process production parameters and ceramsite product requirements, the disc granulator is used for ball making. If the particle size of the raw ball is too large, the diffusion path of the tin inside the ball material becomes longer, resulting in incomplete volatilization of the tin, and the overly large raw ball will make the sintering heat uneven, affecting the uniform expansion and pore structure of the ceramsite, resulting in poor expansion effect of the ceramsite, reducing its light and high-strength performance; if the particle size of the raw ball is too small, although the volatilization path of the tin can be shortened, the material ball is prone to kiln agglomeration in the kiln, hindering the long-term stable production of the rotary kiln, and the particle size is too small, which may cause the gas to be unable to expand effectively during the sintering process, thereby affecting the expansion effect of the ceramsite, and the application range of ceramsite with too small particle size will also be limited.
[0018] As a preferred solution, the drying is carried out by combining rotary kiln waste heat drying and microwave drying, and the drying is carried out to control the moisture content of the ball material to ≤3wt.%. By controlling the moisture content of the ball material at a lower level, the risk of the ball material bursting during the subsequent roasting process can be reduced.
[0019] As a preferred solution, the externally blended coal is supplied at the tail of the rotary kiln; the mass of the externally blended coal accounts for 40% to 70% of the mass of the dry pellets. On the one hand, the externally blended coal is used to provide heat for combustion. By controlling the air volume supplied by the fan, the combustion rate of the externally blended coal is controlled to achieve temperature regulation in the kiln. On the other hand, it is used to create a reducing atmosphere. By controlling the balance between the oxygen consumption of the externally blended coal combustion and the oxygen supply of the fan, the kiln as a whole is ensured to be in a reducing atmosphere. If the amount of externally blended coal added is too little, the coal will be completely burned or the amount of coal will be insufficient, resulting in a drop and fluctuation in the kiln temperature. If the amount of externally blended coal added is too little, the kiln temperature will drop and fluctuate due to the complete combustion of the coal or the insufficient amount of coal. If the amount of externally blended coal added is too much, it will occupy the space of the kiln cavity, resulting in a decrease in the processing volume. In addition, too much externally blended coal in the roasted product will also increase the workload of sorting.
[0020] As a preferred solution, during the two-stage roasting process, the temperature of the first stage roasting is controlled between 800°C and 900°C, and the roasting time is 30 to 60 minutes; the temperature of the second stage roasting is controlled between 900°C and 1000°C, and the roasting time is 20 to 40 minutes. The temperature of the first stage roasting is relatively low, mainly for the volatilization of tin. At this time, only a very small amount of local liquid phase is generated in the ceramsite, which can promote the transformation and decomposition of garnet and does not hinder the volatilization of tin; the temperature of the second stage roasting is relatively high, mainly for the generation of ceramsite. At this temperature, the amount of liquid phase increases and the overall mineral phase regeneration behavior begins to occur, forming a ceramsite supporting skeleton structure such as mullite phase, spinel phase, calcium silicate phase, etc., and has a significant encapsulation effect on the gas, realizing the expansion effect on the ceramsite.
[0021] As a preferred solution, the physical separation includes screening and dry wind magnetic separation; the physical separation process is: the roasted solid product is first screened through a 5mm screen, the screened product is used as ceramsite powder after passing through a high-pressure roller mill, and the screened product is separated into ceramsite products and coal blocks through dry wind magnetic separation, and the coal blocks are used as external coal. Since the reduction volatilization of tin is collected together with the smoke, and the powdered amount in the final roasted solid product accounts for a very small proportion, mainly block-shaped coarse and fine particle size ceramsite and bituminous coal, in the -5mm screened product, mainly ceramsite powder and incompletely burned bituminous coal fine block materials are mainly used. If it is directly put into the rotary kiln for re-roasting, it is very easy to produce a large amount of powdered material to cause kiln agglomeration, and cause the tin grade in the smoke collection system to decrease, and also reduce the air permeability of the roasted material in the kiln, hindering the volatilization of tin, so the ceramsite powder is returned to the raw material for ceramsite preparation through it.
[0022] As a preferred solution, the particle size of the output of the high-pressure roller mill is controlled at -100 meshes, with a mass proportion of ≥60%. If the particle size of the ceramsite powder is not controlled and used for ceramsite preparation, the excessively large bituminous coal particles will lead to incomplete combustion, reducing the strength and durability of the ceramsite, and the excessively large coal particles will release heat in a concentrated manner, causing cracks or irregular shapes in the ceramsite, affecting the expansion effect and performance.
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0024] (1) The present invention treats red mud and tin-containing tungsten tailings in a coordinated manner according to the raw material components, utilizes the physical phase in the red mud to promote the physical phase transformation of the garnet shell, thereby promoting the volatilization of the tin encapsulated therein, and increases the reduction volatilization recovery rate of tin to more than 95%, and greatly reduces the roasting energy consumption;
[0025] (2) Based on the pyrometallurgical tin recovery, the present invention successfully makes the roasted product into high-strength and lightweight ceramsite through raw material regulation and dual-temperature zone continuous reduction roasting, realizing the high-value utilization of roasted slag, which has reference significance for the construction of tailing-free mines and the disposal of red mud;
[0026] (3) The present invention uses a set of processes in a coordinated manner to obtain two products, namely, tin-rich fly ash and high-strength lightweight ceramsite. Compared with the simple pyrometallurgical reduction roasting method for tin removal, the roasting cost is greatly reduced and the economic feasibility is extremely high.
[0027] (4) The present invention utilizes tin-containing tungsten tailings and red mud for synergistic treatment, and the tin recovery rate in the tin-containing tailings is ≥95%. At the same time, the diameter of the finished ceramsite is between 7 and 14 mm, and the bulk density is between 600 and 800 kg / m 3 The cylinder pressure strength is ≥6.0MPa and the 1h water absorption rate is ≤5.50%, which meets the standard requirements of 700 or 800 high-strength light coarse aggregate (GB / T17431.1-2010). DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below through specific embodiments and comparative examples to more clearly demonstrate the purpose, technical solution and advantages of the present invention.
[0029] A tin-containing tungsten tailing in southern Hunan was selected as the research object, and its main chemical components were: Sn content 0.44wt.%, Fe2O3 content 7.42wt.%, SiO2 content 55.13wt.%, Al2O3 content 6.92wt.%, CaO content 6.11wt.%, and fineness -200 mesh was 76%; red mud from Guangxi was selected as the collaborative material, with Fe2O3 content 27.11wt.%, SiO2 content 10.71wt.%, Al2O3 content 17.21wt.%, CaO content 11.42wt.%, Na2O content 6.55wt.%, and fineness -100 mesh was 83%; silicon powder was taken from an industrial silicon smelter in Guangxi, with an SiO2 content of 88.31wt.%; coal powder, silicon carbide, quicklime, and bituminous coal were commercially available industrial grade, among which the coal powder fineness -100 mesh was 87%.
[0030] Ceramic aggregate performance test is carried out according to GB / T17431.2-2010 standard:
[0031] (1) Bulk density: Take 40L of ceramsite, put it into a drying oven and dry it to constant weight, and divide it into two parts. Use a sampling spoon or a shovel to evenly pour the ceramsite from 50mm above the container mouth, and let the ceramsite fall naturally without hitting the capacity cylinder. After filling, make the ceramsite at the top of the capacity cylinder mouth into a cone, and then use a ruler to scrape it flat from the center to both sides along the edge of the capacity cylinder. Fill the concave parts of the surface with ceramsite with smaller particle size and weigh it. Calculate according to the following formula.
[0032]
[0033] ρ bu : Bulk density, in kilograms per cubic meter (kg / m3 ), calculated to an accuracy of 1kg / m 3 ;
[0034] m t : The total mass of ceramsite and capacity cylinder, in kilograms (kg);
[0035] m v : The mass of the volumetric cylinder, in kilograms (kg);
[0036] V: The volume of the volume cylinder, in liters (L).
[0037] The arithmetic mean of the two measured values is taken as the test result.
[0038] (2) Cylinder pressure strength: sieve 5L of 5mm-15mm ceramsite, put it into the pressure cylinder with cylinder bottom required by the standard, put it on the concrete test vibration table and vibrate for 3s, then fill the ceramsite to the top of the cylinder mouth, put it on the vibration table and vibrate for 5s, and scrape (or fill) the ceramsite to level the cylinder mouth. Install the guide cylinder and the punching die, and align the lower scale line of the punching die with the upper edge of the guide cylinder. Place the pressure cylinder on the lower platen of the press, align it with the center of the platen, and uniformly load it at a speed of 300N-500N per second. When the punching die is pressed into the depth of 20mm, record the pressure value.
[0039] Calculate according to the following formula.
[0040]
[0041] f a : cylinder compressive strength, in megapascals (MPa);
[0042] P1: The pressure value when the pressing depth is 20mm, in Newton (N);
[0043] P2: stamping die mass, in Newton (N);
[0044] F: Pressure bearing area (i.e. stamping die area F = 10000mm 2 ).
[0045] The cylinder pressure strength is the arithmetic mean of three measured values as the test result. If the difference between the maximum and minimum values of the three measured values is greater than 15% of the average value, re-sample and test.
[0046] (3) Water absorption rate: Take 4L of ceramsite and dry it to a constant weight. Mix the ceramsite evenly and divide it into three equal parts. Weigh them separately and then put them into a container filled with water. If there are particles floating on the water, press them into the water. After the ceramsite is soaked in water for 1 hour, remove it and filter the water for 1-2 minutes. Then pour it on a wrung wet towel. Hold the two ends of the towel with your hands to make it into a groove shape. Let the ceramsite roll back and forth on the towel 8-10 times to make it saturated and dry, and then weigh it. Calculate according to the following formula.
[0047]
[0048] w a : 1h water absorption, %;
[0049] m0: the mass of water-soaked ceramsite, in grams (g);
[0050] m1: mass of dried ceramsite, in grams (g).
[0051] The arithmetic mean of three measured values was taken as the test result.
[0052] Example 1
[0053] The tin-containing tungsten tailings and red mud are dried and sieved, the block material on the screen is crushed and sieved again to ensure that the particle size meets the requirements, the quicklime is put into the mixer and 2.5 times the mass of the quicklime is gradually and slowly added with cold water and stirred, digested in advance and placed to cool, and the ingredients are 65 parts of tin-containing tungsten tailings, 30 parts of red mud, 3 parts of coal powder, 6 parts of silicon powder, 5 parts of quicklime, 1.5 parts of silicon carbide, 12 parts of crushed material under the screen, and 21 parts of water. After the raw materials are mixed, they are mixed in a two-mixing method, and pelletized with a disc pelletizer. The pellet size is controlled between 6 and 9 mm, and the waste heat air flow from the kiln is used for preliminary drying. After drying, the pellets were sent to a microwave dryer to be fully dried to constant weight, and then put into a rotary kiln for roasting. The coal supply method at the kiln tail was adopted, and 50% wt of coal was additionally added according to the mass of the pellets entering the furnace. The first stage roasting temperature was controlled at 840°C, the roasting time was 40min, and the second stage roasting temperature was controlled at 960°C, the roasting time was 30min. The roasted products were first sieved through a 5mm sieve, and the products under the sieve were used as ceramsite powder after being passed through a high-pressure roller mill. The products on the sieve were separated from the ceramsite products and coal blocks by dry wind magnetic separation to obtain the final ceramsite product. The final tin recovery rate was 97.63%, and the ceramsite bulk density was 679kg / m 3 , cylinder pressure strength 6.42MPa, 1h water absorption rate 5.11%.
[0054] Example 2
[0055] The tin-containing tungsten tailings and red mud were dried and sieved, the blocky materials on the screen were crushed and sieved again to ensure that the particle size met the requirements, the quicklime was put into the mixer and 2.5 times the mass of the quicklime was gradually and slowly added with cold water and stirred, digested in advance and left to cool, and the experiment was carried out with 70 parts of tin-containing tungsten tailings, 23 parts of red mud, 5 parts of coal powder, 8 parts of silicon powder, 5 parts of quicklime, 1.5 parts of silicon carbide, 12 parts of crushed materials under the screen, and 21 parts of water by weight. The raw materials were mixed in a two-mixing method after batching, and pelletized with a disc pelletizer. The pellet size was controlled between 6 and 9 mm, and the waste heat air flow from the kiln was used for preliminary drying. After drying, the pellets were sent to a microwave dryer to be fully dried to constant weight, and then put into a rotary kiln for roasting. The coal supply method at the kiln tail was adopted, and 50% wt of coal was added according to the mass of the pellets entering the furnace. The first stage roasting temperature was controlled at 840°C, the roasting time was 40min, and the second stage roasting temperature was controlled at 940°C, the roasting time was 30min. The roasted products were first sieved through a 5mm sieve, and the products under the sieve were used as ceramsite powder after being passed through a high-pressure roller mill. The products on the sieve were separated from the ceramsite products and coal blocks by dry wind magnetic separation to obtain the final ceramsite product. The final tin recovery rate was 96.27%, and the ceramsite bulk density was 607kg / m 3 , cylinder pressure strength 6.14MPa, 1h water absorption rate 4.22%.
[0056] Example 3
[0057] The tin-containing tungsten tailings and red mud were dried and sieved, the block materials on the screen were crushed and sieved again to ensure that the particle size met the requirements, the quicklime was put into the mixer and 2.5 times the mass of the quicklime was gradually and slowly added with cold water and stirred, digested in advance and left to cool, and the experiment was carried out with 60 parts of tin-containing tungsten tailings, 35 parts of red mud, 3 parts of coal powder, 5 parts of silicon powder, 6 parts of quicklime, 2 parts of silicon carbide, 10 parts of crushed materials under the screen, and 21 parts of water by weight. The raw materials were mixed in a two-mixing method after batching, and pelletized with a disc pelletizer. The pellet size was controlled between 6 and 9 mm, and the waste heat air flow from the kiln was used for preliminary drying. The pellets were then sent to a microwave dryer for full drying to constant weight, and then put into a rotary kiln for roasting. The coal supply method at the kiln tail was adopted, and 50% wt of coal was added according to the mass of the pellets entering the furnace. The first stage roasting temperature was controlled at 860°C, the roasting time was 40 minutes, and the second stage roasting temperature was controlled at 980°C, the roasting time was 30 minutes. The roasted products were first sieved through a 5mm sieve, and the products under the sieve were used as ceramsite powder after being passed through a high-pressure roller mill. The products on the sieve were separated from the ceramsite products and coal blocks by dry wind magnetic separation to obtain the final ceramsite product. The final tin recovery rate was 98.11%, and the ceramsite bulk density was 742kg / m 3 , cylinder pressure strength 7.41MPa, 1h water absorption rate 5.37%.
[0058] Example 4
[0059] The tin-containing tungsten tailings and red mud were dried and sieved, the blocky materials on the screen were crushed and sieved again to ensure that the particle size met the requirements, the quicklime was put into the mixer and 2.5 times the mass of the quicklime was gradually and slowly added with cold water and stirred, digested in advance and left to cool, and the experiment was carried out with 65 parts of tin-containing tungsten tailings, 22 parts of red mud, 3 parts of coal powder, 6 parts of silicon powder, 5 parts of quicklime, 1 part of silicon carbide, 15 parts of crushed materials under the screen, and 21 parts of water by weight. The raw materials were mixed in a two-mixing method after batching, and pelletized with a disc pelletizer. The pellet size was controlled between 6 and 9 mm, and the waste heat air flow from the kiln was used for preliminary drying. The pellets were then sent to a microwave dryer for full drying to constant weight, and then put into a rotary kiln for roasting. The coal supply at the kiln tail was adopted, and 50% wt of coal was added according to the mass of the pellets entering the furnace. The first stage roasting temperature was controlled at 890°C, the roasting time was 60min, and the second stage roasting temperature was controlled at 920°C, the roasting time was 40min. The roasted products were first sieved through a 5mm sieve, and the products under the sieve were used as ceramsite powder after being passed through a high-pressure roller mill. The products on the sieve were separated from the ceramsite products and coal blocks by dry wind magnetic separation to obtain the final ceramsite product. The final tin recovery rate was 95.34%, and the ceramsite bulk density was 705kg / m 3 , cylinder pressure strength 6.71MPa, 1h water absorption rate 4.78%.
[0060] Example 5
[0061] The tin-containing tungsten tailings and red mud were dried and sieved, the block materials on the screen were crushed and sieved again to ensure that the particle size met the requirements, the quicklime was put into the mixer and 2.5 times the mass of the quicklime was gradually and slowly added with cold water and stirred, digested in advance and left to cool, and the experiment was carried out with 65 parts of tin-containing tungsten tailings, 30 parts of red mud, 5 parts of coal powder, 5 parts of silicon powder, 7 parts of quicklime, 2 parts of silicon carbide, 12 parts of the crushed materials under the screen, and 21 parts of water by weight. The raw materials were mixed in a two-mixing method after batching, and pelletized with a disc pelletizer. The pellet size was controlled between 6-9mm, and the waste heat air flow from the kiln was used for preliminary drying. The pellets were then sent to a microwave dryer for full drying to constant weight, and then put into a rotary kiln for roasting. The coal supply at the kiln tail was adopted, and 50% wt of coal was added according to the mass of the pellets entering the furnace. The first stage roasting temperature was controlled at 820°C, the roasting time was 60 min, and the second stage roasting temperature was controlled at 980°C, the roasting time was 30 min. The roasted products were first sieved through a 5mm sieve, and the products under the sieve were used as ceramsite powder after being passed through a high-pressure roller mill. The products on the sieve were separated from the ceramsite products and coal blocks by dry wind magnetic separation to obtain the final ceramsite product. The final tin recovery rate was 96.53%, and the ceramsite bulk density was 644 kg / m 3 , cylinder pressure strength 6.35MPa, 1h water absorption rate 5.46%.
[0062] Comparative Example 1
[0063] Compared with Example 1, other conditions remain unchanged, silicon carbide is removed and coal powder is changed to 5 parts, the final tin recovery rate is 97.58%, and the bulk density of ceramsite is 839kg / m 3 , cylinder pressure strength 6.48MPa, 1h water absorption rate 3.86%. The removal of silicon carbide leads to a poor foaming effect, which cannot be compensated even after increasing the coal powder to 5 parts. At this time, the bulk density increases and the cylinder pressure strength increases slightly.
[0064] Comparative Example 2
[0065] Compared with Example 1, other conditions remain unchanged, only the crushed material under the sieve is removed, and the final tin recovery rate is 95.47%, and the bulk density of ceramsite is 775kg / m 3 , cylinder pressure strength 7.13MPa, 1h water absorption rate 3.59%. The proportion of undersize crushed material has little effect on the physical properties of ceramsite, and its main purpose is to re-disposal and utilize the roasting solid waste. Because the undersize crushed material contains a certain amount of coal powder, the removal of the undersize crushed material leads to less coal powder. If the amount of coal powder added is not increased, the tin recovery rate will be lower and the stacking density will be higher.
[0066] Comparative Example 3
[0067] Compared with Example 1, other conditions remain unchanged, only the roasting process is changed to a single roasting at 850°C for 60 min. The final tin recovery rate is 97.82%, and the bulk density of ceramsite is 1446 kg / m 3 , cylinder pressure strength 12.15MPa, 1h water absorption rate 1.93%. The first stage roasting temperature is too low, resulting in too little liquid phase, which cannot wrap the gas to achieve ceramsite expansion.
[0068] Comparative Example 4
[0069] Compared with Example 1, other conditions remain unchanged, only the roasting process is changed to a single roasting at 950°C for 60 min. The final tin recovery rate is 83.31%, and the bulk density of ceramsite is 682 kg / m 3 , cylinder pressure strength 6.53MPa, 1h water absorption rate 4.63%. The first stage of calcination temperature is too high, resulting in a large amount of liquid phase in the ceramsite before the tin is completely volatilized, which hinders the diffusion of tin vapor, and is accompanied by a vitrification solidification effect, which hinders the subsequent volatilization of tin.
[0070] Comparative Example 5
[0071] Compared with Example 1, other conditions remain unchanged, only the pellet diameter is changed to 12-15 mm, and the first roasting time is extended to 60 min. The final tin recovery rate is 87.43%, and the bulk density of ceramsite is 532 kg / m 3, cylinder pressure strength 4.21MPa, 1h water absorption rate 6.14%. The increase of ceramsite ball diameter will lead to the increase of gaps between balls and the decrease of ceramsite packing density, while the increase of ball diameter will make the diffusion distance of internal tin longer and more difficult, and the tin recovery rate will decrease.
[0072] Comparative Example 6
[0073] Compared with Example 1, other conditions remain unchanged, only the pellet ratio is changed to 85 parts of tin-containing tungsten tailings, 8 parts of coal powder, 8 parts of quicklime, 2 parts of silicon carbide, 13 parts of undersize crushed materials, and 23 parts of water. The final tin recovery rate is 87.46%, and the bulk density of ceramsite is 726 kg / m 3 , cylinder pressure strength 2.84MPa, 1h water absorption rate 3.96%, and ceramsite has no magnetism and cannot be effectively and quickly separated from bituminous coal. The removal of red mud leads to the deterioration of the induced destruction of the shell of tin garnet, and there is no iron source to provide magnetism, resulting in a decrease in tin recovery and inability to effectively separate.
[0074] From the comparative examples, it can be seen that tin-containing tungsten tailings and red mud have good synergistic effects in promoting tin volatilization and preparing expanded clay. Through the complementary raw material components and the addition of auxiliary materials, it is achieved that tin reduction volatilization and firing of high-strength and lightweight expanded clay can be completed with one set of processes.
Claims
1. A method for preparing high-strength lightweight ceramsite and recovering tin by synergistically using tin-containing tungsten tailings and red mud, characterized in that: Raw materials including tin-containing tungsten tailings, red mud, coal powder, silicon powder, quicklime, silicon carbide and ceramsite powder are mixed with water to form balls, so as to obtain balls; after the balls are dried, they are transferred to a rotary kiln and mixed with external coal to complete two-stage roasting, during which tin products are recovered from the flue gas, and the solid products obtained by roasting are physically sorted to separate the ceramsite products.
2. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically preparing tin-containing tungsten tailings and red mud according to claim 1, characterized in that: The raw materials include the following components by weight: 60-75 parts of tin-containing tungsten tailings, 20-35 parts of red mud, 3-5 parts of coal powder, 5-10 parts of silicon powder, 3-7 parts of quicklime, 1-2 parts of silicon carbide, and 10-15 parts of ceramsite powder.
3. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically preparing tin-containing tungsten tailings and red mud according to claim 1 or 2, characterized in that: The tin content of the tin-containing tungsten tailings is 0.4-0.6wt.%, Fe2O3 content is 5-10wt.%, SiO2 content is 45-60wt.%, Al2O3 content is 5-10wt.%, and CaO content is 5-10wt.%; The red mud has a Fe2O3 content of 20-30wt.%, a SiO2 content of 5-15wt.%, an Al2O3 content of 12-20wt.%, a CaO content of 5-15wt.%, and a Na2O content of 4-8wt.%.
4. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically preparing tin-containing tungsten tailings and red mud according to claim 1 or 2, characterized in that: The fineness of the tin-tungsten tailings meets the mass content of -200 mesh size ≥ 70%; The fineness of the red mud satisfies that the mass content of the -100 mesh particle size is ≥ 75%; The fineness of the coal powder satisfies that the mass content of the -100 mesh particle size is ≥85%.
5. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically preparing tin-containing tungsten tailings and red mud according to claim 1, characterized in that: The pelletizing is achieved by using a disc pelletizing machine, and the pelletizing controls the particle size of the pellets to be within the range of 6 to 9 mm.
6. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically using tin-containing tungsten tailings and red mud according to claim 1, characterized in that: The drying is carried out by combining rotary kiln waste heat drying and microwave drying, and the drying is carried out to control the moisture content of the ball material to be ≤3wt.%.
7. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically using tin-containing tungsten tailings and red mud according to claim 1, characterized in that: The externally blended coal is supplied from the tail of the rotary kiln; the mass of the externally blended coal accounts for 40% to 70% of the mass of the dry pellets.
8. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically using tin-containing tungsten tailings and red mud according to claim 1, characterized in that: In the two-stage roasting process, the temperature of the first stage is controlled between 800°C and 900°C, and the roasting time is 30 to 60 minutes; the temperature of the second stage is controlled between 900°C and 1000°C, and the roasting time is 20 to 40 minutes.
9. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically using tin-containing tungsten tailings and red mud according to claim 1, characterized in that: The physical separation includes screening and dry wind magnetic separation; the physical separation process is: the roasted solid product is first screened through a 5mm sieve, the screened product is passed through a high-pressure roller mill and used as ceramsite powder material, the screened product is separated into ceramsite products and coal blocks through dry wind magnetic separation, and the coal blocks are used as external coal.
10. The method for preparing high-strength lightweight ceramsite and recovering tin by synergistically using tin-containing tungsten tailings and red mud according to claim 9, characterized in that: The particle size of the material discharged from the high pressure roller mill is controlled at -100 mesh particle size with a mass proportion of ≥60%.
Citation Information
Patent Citations
Lightweight and high-strength ceramsite, preparation method and application thereof
CN112430066A
Method for purifying tin-containing waste and method for reusing tin-containing waste
JP2010042954A
A novel method of producing synthetic lightweight ceramic sand and uses thereof
WO2020109861A2
Method for enriching and recovering chromium resources by synergistic utilization of chromium-containing sludge and chromium-containing waste residue
WO2023004925A1
Cited By
Method for multi-metal reinforced separation of high-tin tailings and preparation of high-quality iron powder
CN120536715A